The right of the unborn against eugenics through the selection of embryosin in vitro fertilization - Galiano Maritan, Grisel; Morffi Collado , Claudia Lorena; León Fadraga, Geanny (Revista Universidad de Guayaquil, 2020)
The analysis of the new eugenics and its use in in vitro fertilization raises serious legaldilemmas between the desire to conceive, the protection of the embryo and the genetic identityand individuality of the unborn. In vitro fertilization, a technique that is part of a medicalprocedure for fertilization using an extracorporeal medium, has been transformed through thepreselection of embryos. The main objective of the research is to analyze the repercussions ofthe application of eugenics as an embryo pre-selection criterion in in vitro fertilization, for thefulfillment of this purpose, methods and techniques of a social investigation of a legal natureare used within which are They find: the historical-logical analysis; the exegetical - analyticalmethod; the comparative method; the case study and, of course, the bibliographic analysis
Keywords: embryo; fertilization; law; eugenic